(untitled) (Revista de Ciências Agroveterinárias, 2023)
Ketosis is a disease that affects high-yielding dairy cattle during the peripartum period, causing clinical and metabolic alterations, and significant productive and economic losses. This study aimed to report three cases of clinical ketosis in dairy cows. The three animals of the Holstein breed, reared in a semi-intensive regime, with a history of 40–45 days postpartum, showed signs of apathy, lack of appetite and drop in milk production. After clinical examination and complementary tests, one case of primary clinical ketosis and two cases of clinical ketosis secondary to left displaced abomasum or anaplasmosis were diagnosed. The animals presented hyperketonemia, ketonuria and normo or hypoglycemia, which were determined by rapid tests. Treatment was instituted with a view to reducing ketogenesis, restoring blood glucose and resolving concomitant diseases, with full clinical and productive recovery. The reports of these cases reinforce the importance of knowing the disease, highlighting the use of rapid tests for the field diagnosis of ketosis, enabling early and accurate treatment, thus contributing to the reduction of damage associated with its occurrence.